2006
DOI: 10.1021/jp060093s
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric Effects in the Gas-Phase Reactions of Dichloroethene, C2H2Cl2, with a Series of Cations

Abstract: : A study of the reactions of a series of gas-phase cations (NH the results suggest that the formation of a collision complex at short range between these ions and C 2 H 2 Cl 2 is responsible for the observed effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(58 citation statements)
references
References 47 publications
5
52
1
Order By: Relevance
“…However, collisional techniques based on electron and ion impact had varying degrees of success in linking changes in molecular geometry to dynamical processes. In most cases, the isomers produced similar mass spectra [3][4][5][6]. Electron scattering from isomers has only recently demonstrated convincing differences in the absolute total cross sections in the low-energy region [7].…”
mentioning
confidence: 92%
“…However, collisional techniques based on electron and ion impact had varying degrees of success in linking changes in molecular geometry to dynamical processes. In most cases, the isomers produced similar mass spectra [3][4][5][6]. Electron scattering from isomers has only recently demonstrated convincing differences in the absolute total cross sections in the low-energy region [7].…”
mentioning
confidence: 92%
“…The upper limit arises due to the possible presence of an exit-channel barrier and/or a kinetic shift; if both are zero, the conversion is exact. This procedure was developed for interpretation of photoionisation yields rather than state-selected TPEPICO yields, but we have shown that the procedure is equally valid for both experiments [29,30]. For the vibrational frequencies of SF 5 + and SF 4 Cl + needed for these conversions, values for the isoelectronic neutral molecules PF 5 and PF 4 Cl were used [31,32]; the differences of the vibrational frequencies due to a change in reduced mass of the sulphur and phosphorus analogues make negligible difference to these conversions.…”
Section: Data Analysis and Energeticsmentioning
confidence: 99%
“…The only ion which shows a significant variation from the TPEPICO branching ratios is N + (RE = 14.53 eV), as observed in previous work. 1,14 It appears that reaction with N + causes much 'softer' ionisation ( i.e. less fragmentation)…”
Section: Comparison Of Tpepico and Sift Branching Ratiosmentioning
confidence: 99%